The Influence of Organizational Communication on Employee Performance Mediated by Employee Job Satisfaction at the Denpasar City Health Office - Anak Agung Gde Wimanta Wari Bawantu; I Gusti Made Suwandana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research took the location, namely the Denpasar City Health Service. Within the company there are 5 fields available to support integrated health service programs for the community, with a total human resource population of 61 emoployee. The health development program has been implemented with reference running into half decade Strategic Planning which is outlined in the annual performance plan. The health development was carried out in the form of 18 existing health development programs. The pre-survey results showed the influence of employee performance variables using seven questions. 14 samples said they did not agree to the seventh question, 5 respondents answered by choosing the word